2013
DOI: 10.14356/kona.2013016
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Inverse Gas Chromatography and its Development as a Tool to Characterize Anisotropic Surface Properties of Pharmaceutical Solids

Abstract: Surface properties can profoundly impact the bulk and interfacial behavior of pharmaceutical solids, and also their manufacturability, processability in drug product processes, dissolution kinetics and mechanism in drug delivery. Variation in the inter-and intra-molecular interactions gives rise to anisotropic surface properties of crystalline solids which display direction-dependent characteristics relative to the orientation of the crystal unit structure. Despite its establishment since the 1950s, inverse ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 80 publications
(85 reference statements)
4
61
0
Order By: Relevance
“…This manifests itself in some surface energy profiles (see SI figure S6) where the surface energy plateaus before beginning to increase with coverage. This is generally accompanied by peak fronting in the chromatograms which has been associated with probe-probe interactions by Ho et al 29 Where such increases were observed, we removed the relevant data points and only analysed data where the measured surface energy falls or stays constant with increasing probe coverage. While this should minimise the effect of probe-probe 6 interactions, we cannot avoid the fact that surface energy values in the high coverage regime may be slightly over estimated.…”
Section: Inverse Gas Chromatography Theorymentioning
confidence: 99%
“…This manifests itself in some surface energy profiles (see SI figure S6) where the surface energy plateaus before beginning to increase with coverage. This is generally accompanied by peak fronting in the chromatograms which has been associated with probe-probe interactions by Ho et al 29 Where such increases were observed, we removed the relevant data points and only analysed data where the measured surface energy falls or stays constant with increasing probe coverage. While this should minimise the effect of probe-probe 6 interactions, we cannot avoid the fact that surface energy values in the high coverage regime may be slightly over estimated.…”
Section: Inverse Gas Chromatography Theorymentioning
confidence: 99%
“…To measure the total surface energy of any material we can crudely sum the dispersive term, γ D , and the specific terms, γ sp . 43 γ sp can be determined using IGC, as ΔG sp using: ) i.e. the difference of RTlnV n for the specific probe and the corresponding dispersive reference line (as shown in figure 3a).…”
Section: Thermodynamic Prediction Of Organic Solvents For Bc Dispersionsmentioning
confidence: 99%
“…PXRD is a well-established technique for quantification of percentage crystallinity existing initially or transformed during manufacturing [151]. X-ray photoelectron scattering (XPS) [152] and inverse gas chromatography (IGC) [153] are very sensitive techniques for surface analysis and anisotropy. DVS plays an important role in calculating the hygroscopicity and the level of intermolecular interactions [154], while TGA may be used to calculate the moisture level in the solid form.…”
Section: Solid State Characterization Of Hydrates Solvates and Amorpmentioning
confidence: 99%